2016
DOI: 10.1016/j.vetmic.2016.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of four recombinant fimbrial proteins of virulent Aeromonas hydrophila strain ML09-119 in channel catfish

Abstract: Aeromonas hydrophila is a reemerging pathogen of channel catfish (Ictalurus punctatus); recent outbreaks from 2009 to 2014 have caused the loss of more than 12 million pounds of market size catfish in Alabama and Mississippi. Genome sequencing revealed a clonal group of A. hydrophila isolates with unique genetic and phenotypic features that is highly pathogenic in channel catfish. Comparison of the genome sequence of a representative catfish isolate (ML09-119) from this virulent clonal group with lower virulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…All fish experiments were conducted in accordance with a protocol approved by the Institutional Animal Care and Use Committee at Mississippi State University. Virulence of vAh Δ hcp1 and vAh Δ vgrG1 was compared to A. hydrophila wild-type (WT) strain ML09-119 by immersion route of exposure as described (Abdelhamed et al, 2016). Briefly, 120 6-month-old specific-pathogen-free (SPF) channel catfish fingerlings (18.10 ± 0.56 cm, 50.90± 3.76 g) were stocked into twelve 40-liter flow-through tanks (10 fish/tank) and acclimated for a week.…”
Section: Methodsmentioning
confidence: 99%
“…All fish experiments were conducted in accordance with a protocol approved by the Institutional Animal Care and Use Committee at Mississippi State University. Virulence of vAh Δ hcp1 and vAh Δ vgrG1 was compared to A. hydrophila wild-type (WT) strain ML09-119 by immersion route of exposure as described (Abdelhamed et al, 2016). Briefly, 120 6-month-old specific-pathogen-free (SPF) channel catfish fingerlings (18.10 ± 0.56 cm, 50.90± 3.76 g) were stocked into twelve 40-liter flow-through tanks (10 fish/tank) and acclimated for a week.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial bath challenge was conducted as described previously ( Abdelhamed et al, 2016 ). Briefly, the water level in each tank was dropped to 10 l, and 100 ml of overnight culture was added to each tank to yield approximately 4.3 × 10 10 CFU/ml water.…”
Section: Methodsmentioning
confidence: 99%
“…Several research groups have identified candidate DNA or recombinant protein vaccines for MAS (2328), but to date, there is no protective vaccine available against MAS caused by vAh. Previously, we purified four fimbrial proteins (FimA, Fim, MrfG, and FimOM) and three outer membrane proteins (major outer membrane protein OmpA1, TonB-dependent receptor, and transferrin-binding protein A) and assessed their ability to stimulate protective immunity in channel catfish fingerlings against vAh infection (17, 29). In the present study, expression and purification of vAh ATPase protein in E. coli were successful, and purified ATPase protein was recovered from the inclusion body.…”
Section: Discussionmentioning
confidence: 99%
“…At 3 weeks post-immunization, catfish were experimentally infected by bath immersion with 2.8 × 10 10 CFU/ml of A. hydrophila ML09-119 for 6 h at 30°C (17). Bacterial infection dose was chosen based on previous experimental infection doses (8, 18).…”
Section: Methodsmentioning
confidence: 99%